Dryops renateae Greń & Przewoźny sp. n. from Tajikistan (Coleoptera: Dryopidae) - Greń, Czesław; Przewoźny, Marek; Szczepański, Wojciech T.; Karpiński, Lech (Zootaxa, 2016)
The genus Dryops Olivier, 1791 has a worldwide distribution. In the Palaearctic region, it contains 34 species, from Tajikistan only one was recorded so far—Dryops rufipes Krynicki, 1832 (Olmi 1976, Kodada & Jäch 2006). During an expedition of last two authors to the Tajikistan in 2014 a series of new species was found, which is described in this paper.